Glycomacropeptide for nutritional management of phenylketonuria: a randomized, controlled, crossover trial - Ney, Denise M; Stroup, Bridget M; Clayton, Murray K; Murali, Sangita G; Rice, Gregory M; Rohr, Frances; Levy, Harvey L (The American journal of clinical nutrition, 2016)
To prevent cognitive impairment, phenylketonuria requires lifelong management of blood phenylalanine (Phe) concentration with a low-Phe diet. The diet restricts intake of Phe from natural proteins in combination with traditional amino acid medical foods (AA-MFs) or glycomacropeptide medical foods (GMP-MFs) that contain primarily intact protein and a small amount of Phe. We investigated the efficacy and safety of a low-Phe diet combined with GMP-MFs or AA-MFs providing the same quantity of protein equivalents in free-living subjects with phenylketonuria. This 2-stage, randomized crossover trial included 30 early-treated phenylketonuria subjects (aged 15-49 y), 20 with classical and 10 with variant phenylketonuria. Subjects consumed, in random order for 3 wk each, their usual low-Phe diet combined with AA-MFs or GMP-MFs. The treatments were separated by a 3-wk washout with AA-MFs. Fasting plasma amino acid profiles, blood Phe concentrations, food records, and neuropsychological tests were obtained. The frequency of medical food intake was higher with GMP-MFs than with AA-MFs. Subjects rated GMP-MFs as more acceptable than AA-MFs and noted improved gastrointestinal symptoms and less hunger with GMP-MFs. ANCOVA indicated no significant mean ± SE increase in plasma Phe (62 ± 40 μmol/L, P = 0.136), despite a significant increase in Phe intake from GMP-MFs (88 ± 6 mg Phe/d, P = 0.026). AA-MFs decreased plasma Phe (-85 ± 40 μmol/L, P = 0.044) with stable Phe intake. Blood concentrations of Phe across time were not significantly different (AA-MFs = 444 ± 34 μmol/L, GMP-MFs = 497 ± 34 μmol/L), suggesting similar Phe control. Results of the Behavior Rating Inventory of Executive Function were not significantly different. GMP-MFs provide a safe and acceptable option for the nutritional management of phenylketonuria. The greater acceptability and fewer side effects noted with GMP-MFs than with AA-MFs may enhance dietary adherence for individuals with phenylketonuria. This trial was registered at www.clinicaltrials.gov as NCT01428258.